Mekanisme Penyelesaian Kredit Macet dan Implikasinya terhadap Nasabah di PT. Adira Dinamika Multi Finance Cabang Pamekasan - Maisaroh, Siti; Qomariyah, Noviyatul (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
Non-performing loans (NPLs) in consumer finance institutions are a critical issue that can affect financial stability and the continuity of business operations. In the Madura region, motorcycles have become a primary necessity. However, due to limited financial capacity, people tend to rely on credit facilities provided by financing institutions such as PT Adira Dinamika Multi Finance, Pamekasan Branch. This study aims to analyze the mechanisms used to resolve non-performing loans and examine their implications for customers from an Islamic economic perspective. The research employs a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that PT Adira implements persuasive approaches, such as issuing warnings and engaging in negotiations, along with credit restructuring as initial steps to address problematic loans before resorting to legal measures. From the Islamic economic perspective, resolving non-performing loans should not only focus on institutional interest but must also uphold justice, public benefit (maslahah), and the debtor's moral responsibility. This reflects the importance of integrating Islamic ethical values into the governance of consumer financing, aiming to achieve a balance between financial goals and humanitarian values